Coronavirus Precautions: Experience of High Volume Liver Transplant Institute - Başkıran, Adil; Akbulut, Sami; Şahin, Tevfik Tolga; Tunçer, Adem; Kaplan, Kuntay; Bayındır, Yasar; Yılmaz, Sezai (Turkish Journal of Gastroenterology, 2022)
Background: To present the struggle of a high volume liver transplant center against coronavirus infectious disease-2019 pandemic. Methods: Between March 2020 and December 2020, the demographic and clinical data of staff and liver transplant candidates diagnosed with coronavirus infectious disease-2019 in our Liver Transplant Institute were prospectively analyzed. Results: First, 32 healthcare staff were diagnosed with coronavirus infectious disease-2019, and 6 of them were surgeons. Six staff were asymptomatic, while 24 staff had mild or moderate and 2 staff had severe coronavirus infectious disease-2019. All the staff recovered from the disease without any permanent sequela and returned to duty after 2 consecutive negative polymerase chain reaction results within 24-hour intervals. Second, during the preoperative investigation, 6 living liver donor candidates and 13 recipients were tested positive for coronavirus infectious disease-2019 (son = 6, unrelated = 3, cousin = 3, daughter = 2, cadaveric = 1). Eleven patients received favipiravir and 8 did not receive any treatment because they were asymptomatic. Only one recipient who had severe coronavirus infectious disease-2019 died due to multiple organ failure syndrome. One recipient died in the early postoperative period. The median duration from the initial diagnosis of the patients till the transplant procedure was 21 days (min-max: 14-105 days). During the time of operation, the polymerase chain reaction tests of the donors and the recipients were negative, and the thorax tomography images showed no signs of viral pneumonia. Conclusion: Meticulous precautions, multidisciplinary approach, team effort, and organization of facilities can increase the quality of care of these patients in the coronavirus infectious disease-2019 era. Healthcare workers have shown tremendous effort and are the true heroes of this era. Cite this article as: Başkıran A, Akbulut S, Şahin TT, et al. Coronavirus precautions: Experience of high volume liver transplant institute. Turk J Gastroenterol. 2022;33(2):145-152.